(untitled) (Revista de Ciências Agroveterinárias, 2024)
Ponds built on land are the main production units for aquatic organisms and the characteristics of the base soil of these structures influence the quality of water and the aquatic ecosystem formed for production. The objective of this study is to verify the characteristics of fish farms’ soils and address their importance for fish farming. The study was based on the collection of base soils for the construction of fish ponds in the city of Dourados - MS, Brazil. Particle size, pH, organic matter (OM), effective (t) and potential cation exchange capacity (T), base saturation (V%), and aluminum saturation (m%) were evaluated. There was a significant positive correlation between pH x V% (0.77) and V% x t (0.74). There were significant negative correlations between the chemical variables pH x m% (-0.87), V% x m% (-0.88) and physical variables with clay in relation to sand (-0.91) and silt (-0.83). The correlation results corroborated the clusters formed by the PCA analysis, which indicated the existence of three groups of variables considering the first two dimensions. A negative relationship of m% x pH and V% was evident. When performing the grouping of properties according to soil parameters, three groups formed. This shows that even properties built on soils of a same pattern, such as a floodplain site, may show differences in physical, chemical, and soil organic matter parameters.